What drives the ethical acceptance of deep synthesis applications? A fuzzy set qualitative comparative analysis. (August 2022) - Li, Minghui; Wan, Yan; Gao, Jinping
Abstract: The beneficial aspects of deep synthesis applications are evident in innovations like virtual anchors, film post-production, and virtual fitting. However, this technology also has malicious applications that present ethical challenges, including pornography, voice fraud, and political defamation. Determining why some deep synthesis applications are considered ethically acceptable while others are not can help to identify whether an application deserves encouragement or regulation, and to promote positive and curb negative applications. This is essential for the responsible innovation of deep synthesis. This study builds on anticipatory technology ethics to explore how ethical conditions ( rights, justice, well-being and common good, no-harm, and responsibility ) can be combined as causal configurations to explain the ethical acceptance of deep synthesis. We employ a fuzzy set qualitative comparative analysis to analyze data from sixteen selected deep synthesis application cases. The results show four ethical critical configurations, summarized into three paths: utilitarianism, deontology, and the bottom line. Well-being and common good, no-harm, and responsibility are the core conditions for high ethical acceptance. This study unpacks the complexity of factors underlying the ethical acceptance of deep synthesis and provides a reference for future ethical reviews of deep synthesis applications to ensure responsible development. Highlights: Ethical principles' configurations lead to the acceptance of deep synthesis applications. Ethical acceptance is based on the psychology of utilitarianism, deontology and bottom-line. Well-being and common good, justice, and no-harm are the core conditions of high ethical acceptance. The influence path of ethical acceptance provides a reference for ethical review of deep synthesis applications.